Evaluation of the clinical efficiency of tocilizumab versus rituximab therapy in patients with rheumatoid arthritis - Anastasia Sergeyevna Avdeyeva (Научно-практическая ревматология, 2012)
Objective: to evaluate the clinical efficiency of tocilizumab (TCZ) versus rituximab (RTM) therapy using DAS 28, SDAI, and CDAI scores and to estimate remission rates using DAS 28 and the remission criteria proposed by the European League Against Rheumatism (EULAR) and the American College of Rheumatology (ACR) in 2011. Subjects and methods. Seventy-six patients with rheumatoid arthritis (RA) divided into 2 groups were examined. Group 1 included 42 patients receiving six TCZ infusions in an intravenous dose of 8 mg/kg at a 4-week interval during stable therapy with disease-modifying antirheumatic drugs (DMARDs) and glucocorticosteroids (GC); Group 2 comprised 34 persons who were given two RTM infusions in intravenous doses of 500 and 1000 mg at 2-week interval during therapy with DMARDS and GC in 12 (35%) and 22 (65%) patients, respectively. The EULAR criteria and SDAI and CDAI scores were used to evaluate therapeutic effectiveness. Remission was assessed using the EULAR criteria and the new 2011 EULAR/ACR remission ones. Results. In Group 1, the baseline DAS 28, SDAI, and CDAI scores were 6.44 [5.87; 7.04], 45.0 [36.2; 57.0], and 41.5 [32.0; 53.0]; in Group 2, these were 6.12 [5.52; 6.81], 34.3 [23.8; 45.9], and 31.3 [21.8; 38.5], respectively. At week 24 of therapy, Groups 1 and 2 patients achieved a DAS 28 remission in 71 and 23.5% of cases, a SDAI remission in 31 and 14.7%, and a CDAI remission in 33 and 17.6%, respectively. In the RTM-treated patients who had not previously received therapy with genetically engineered biological agents (GEBAs), DAS 28, SDAI, and CDAI remissions were observed more frequently (38, 23.8, and 28.6%, respectively) than in those receiving GEBAs (0%; p < 0.01) and their rate was comparable with that in Group 1 patients (according to SDAI and CDAI scores). In Groups 1 and 2, the remission rates according to the 2011 ACR/EULAR criteria were 24 and 11.8%, respectively. Conclusion. The results obtained during a 24-week trial are indicative of the high clinical efficiency of TCZ and RTM therapy. The number of TCZ-treated patients who had achieved a DAS 28 remission were much more while SDAI and CDAI remission rates among the patients who had not previously received GEBAs were virtually comparable with those when TCZ and RTM were administered.